ANALISIS STABILITAS LERENG DINDING PENAHAN TANAH MENGGUNAKAN SOFTWARE GEO5 PADA AKSES JALAN PLTMH LAMPUNG - Yuono, Teguh; Arumningsih , Dian; Reki Arbianto; Kasih, Mutiara; Fakiq, Thoha (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Micro Hydro Power Plant (PLTMH) is one of the solutions in meeting the needs of renewable energy, especially in remote areas that have abundant water resource potential. This study aims to analyze slope stability and analyze the budget plan for building a retaining wall with a cantilever wall or gravity wall type. The method used in this study is using GEO5 software and calculating the budget plan (RAB). The results of this study using retaining wall analysis using GEO5 Software with the Cantilever Wall type get the Safety Factor results: 1.87> 1.10, the results of retaining wall analysis using GEO5 Software with the Gravity Wall type get the Safety Factor results: 2.03> 1.10. And the results of the RAB recapitulation using the Cantilever Wall type compact the results: Rp 6,469,724,186, and the results of the RAB recapitulation using the Gravity Wall type compact the results: Rp 2,445,607,393. So the most efficient RAB result is using the Gravity Wall type.